Cytotoxic and Antimetastasis Effect of Ethyl Acetate Fraction from Caesalpinia sappan L. on MCF-7/HER2 Cells - Riris Istighfari Jenie; Sri Handayani; Ratna Asmah Susidarti; Zalinar Udin; Edy Meiyanto (Indonesian Society for Cancer Chemoprevention, 2017)
Overexpression of HER2 in breast cancer cell is found on invasive breast cancer and correlated with worse prognosis. Caesalpinia sappan L shows cytotoxic activity on various cancer cells. The goal of this research is to determine the cytotoxic activity and inhibition of migration and invasion of ethyl acetate fraction of Caesalpinia sappan L. (FEA) on HER2 overexpression-breast cancer cells (MCF-7/HER2). The MTT and flow cytometry assay showed that FEA revealed cytotoxic effect in a dose-dependent manner (IC50= 34 ± 3.1 µg/ml) and induced apoptosis, S and G2/M phase accumulation. Wound healing assay, gelatin zymography and immunoblotting assay showed that FEA inhibited migration and suppressed MMP2, MMP9, HER2 and Rac1 protein level. Thus, ethyl acetate fraction of Caesalpinia sappan L. is potential to be developed on future research especially to treat metastatic breast cancer with HER2 overexpression.Keywords: Ethyl acetate fraction of Caesalpinia sappan L, cytotoxic effect, migration and invasion, MCF-7/HER2 cells